Assessment of Leachate Treatment Efficiency and Its Impact on Surface Water Quality at the Blang Bintang Landfill, Aceh Besar - Jonianto Jonianto; Ichwana Ramli; Suhendrayatna Suhendrayatna; Sri Mulyati; Mariana Mariana (The University of Lampung, 2026)
This study aims to evaluate the effectiveness of the leachate treatment plant at the Blang Bintang Regional landfill and analyze its impact on the water quality of the Krueng Uteun Siblah River. The method used is a comparative analysis of leachate quality monitoring data (influent and effluent) from the landfill from 2021 to 2025. The results showed that the treatment plant successfully reduced the concentration of pollutants in leachate, with an average efficiency percentage for the parameters of Chemical Oxygen Demand (COD), Biological Oxygen Demand (BOD), and Total Suspended Solids (TSS) Nitrate, NH₃, Cd, Fe were 23.87%, 64.15%, 50.53%, 35.26%, 62.19%, 71.05%, and 40.18%, respectively. However, effluent values for COD and BOD parameters still exceed the established quality standards. Further analysis of the Krueng Uteun Siblah River revealed a significant decline in water quality immediately after the leachate outfall point, marked by a spike in BOD (27.4-30 mg/L), COD (51.17-62 mg/L), and iron concentration (3.65-4.21 mg/L) that exceeded quality standards, as well as a drastic decrease in Dissolved Oxygen (DO) levels to 3.5 mg/L improving the performance of leachate treatment facilities and implementing stricter management strategies are absolutely necessary to protect the aquatic ecosystem around the landfill.